Factors associated with breast lymphedema after adjuvant radiation therapy in women undergoing breast conservation therapy - Summer Sami Yono; Cara Cannella; Madeleine Gonte; Sanjay Rama; Simeng Zhu; Jenna Luker; Maristella S. Evangelista; Jessica Bensenhaver; Eleanor M. Walker; Dunya Atisha (Breast)
Purpose: Breast lymphedema after post-lumpectomy radiation therapy (RT) is poorly defined and difficult to treat. The aim of this study was to define the incidence of breast lymphedema and identify factors associated with the risk of developing breast lymphedema (BL) in women undergoing breast-conserving therapy. Methods: A retrospective cohort study of patients with early-stage breast cancer who underwent breast-conserving surgery (lumpectomy) followed by RT between January 1, 2014 and July 31, 2019 at a single institution. Women who developed BL, defined as swelling of the breast persisting ≥1 year after RT, were compared with women who did not. Univariate and multivariate regression analyses were used to identify factors associated with risk of BL. Results: A total of 1052 patients were included in the study: 99 (9.6 %) developed BL and 953 (90.6 %) did not develop BL. The mean ± standard deviation age was 62.9 ± 11.1 years and the mean breast volume was 1352.0 ± 744.9 cm3. Patients with breast volume ≥1500 cm3 (adjusted odds ratio [aOR] = 2.34; 95 % CI, 1.40–3.91; p = 0.001), Black patients (aOR = 1.78; 95 % CI, 1.12–2.82; p = 0.015), those who received neoadjuvant (aOR = 3.05; 95 % CI, 1.28–7.30; p = 0.012) or adjuvant chemotherapy (aOR = 2.14; 95 % CI, 1.29–3.55; p = 0.003), those with postoperative cellulitis (aOR = 3.94; 95 % CI, 2.20–7.06; p < 0.001), and women who developed arm lymphedema (aOR = 2.94; 95 % CI, 1.50–5.77; p = 0.002) had significantly higher odds of developing BL. Conclusion: Patients with larger breast volumes, Black patients, those receiving chemotherapy, and those who develop arm lymphedema or cellulitis may be at higher risk of BL after lumpectomy and RT, suggesting that patients with these risk features may benefit from complementary or alternative surgical approaches and heightened monitoring to avoid BL.